Supertetrahedral anions in the phosphidosilicates Na1.25Ba0.875Si3P5 and Na31Ba5Si52P83. Issue 26 (11th June 2021) - Haffner, Arthur; Zeman, Otto E. O.; Bräuniger, Thomas; Johrendt, Dirk
Abstract : New phosphidosilicates form complex supertetrahedral structures with channels for sodium ion conduction. Abstract : Solid ionic conductors are one key component of all-solid-state batteries, and recent studies with lithium, sodium and potassium phosphidosilicates revealed remarkable ion conduction capabilities in these compounds. We report the synthesis and crystal structures of two quaternary phosphidosilicates with sodium and barium, which crystallize in new structure types. Na1.25 Ba0.875 Si3 P5 contains layers of T3 supertetrahedra, while Na31 Ba5 Si52 P83 forms defect T5 entities and contains Si–Si bonds and P3 trimers. Though T 1 -relaxometry data indicate a relatively low activation energy for Na + migration of 0.16 eV, the crystal structures lack sufficient three-dimensional migration paths necessary for fast sodium ion conductvity.